The impact of severing diplomatic relations on economic relations - suhil, marwan mohammed (The International and Political Journal, 2025)
With the increasing importance of the economy as an important means of managing international relations, the importance of international economic relations has emerged, which has grown in the context of increasing international competition. Here, diplomacy works to enrich its traditional and well-known focus by strengthening trade and investment relations, which have proven to be a priority element in international relations in the twenty-first century. Traditional diplomacy is practiced as an art and craft of communication and exchange between countries through their diplomatic representatives to achieve national interests, whether political, economic, social, or other interests using peaceful means. However, it does not exclude the use of economic pressure to achieve political goals, by exploiting individual or collective diplomatic means at the level of international, regional, and global organizations to achieve political goals. Thus, the continuity and stability of diplomatic relations are directly or indirectly reflected in economic relations.